2022
DOI: 10.1002/cpt.2635
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Scores for Blood Pressure to Assess the Risk of Severe Bevacizumab‐Induced Hypertension in Cancer Patients (Alliance)

Abstract: Hypertension is a common bevacizumab-induced toxicity. No markers are available to predict patients at risk of developing hypertension. We hypothesized that genetic risk of essential hypertension, as measured by a blood pressure polygenic risk score (PRS), would be associated with risk of severe bevacizumab-induced hypertension. PRSs were calculated for 1,027 bevacizumab-treated patients of European descent with cancer from four clinical trials (Alliance for Clinical Trials in Oncology (Alliance) / Cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Previously, a PRS constructed utilizing genome-wide important single nucleotide polymorphisms from GWAS for BP showed a significant relationship with heart failure, left ventricular mass, coronary artery disease and stroke (Studies, 2011 ; Ference et al, 2014 ). Currently, there is considerable excitement in the field for developing reliable PRS for HTN as evident from multiple reports of PRS indices from different cohorts (Steinthorsdottir et al, 2020 ; Sapkota et al, 2021 ; Sato et al, 2021 ; Fujii et al, 2022 ; Parcha et al, 2022 ; Quintanilha et al, 2022 ). Recently, Weng et al ( 2022 ) included 391,366 participants from the UK Biobank database and established a PRS for HTN assessing the combined effect of genetic susceptibility and air pollution on incident of HTN.…”
Section: From Gwas To Prs For Htnmentioning
confidence: 99%
“…Previously, a PRS constructed utilizing genome-wide important single nucleotide polymorphisms from GWAS for BP showed a significant relationship with heart failure, left ventricular mass, coronary artery disease and stroke (Studies, 2011 ; Ference et al, 2014 ). Currently, there is considerable excitement in the field for developing reliable PRS for HTN as evident from multiple reports of PRS indices from different cohorts (Steinthorsdottir et al, 2020 ; Sapkota et al, 2021 ; Sato et al, 2021 ; Fujii et al, 2022 ; Parcha et al, 2022 ; Quintanilha et al, 2022 ). Recently, Weng et al ( 2022 ) included 391,366 participants from the UK Biobank database and established a PRS for HTN assessing the combined effect of genetic susceptibility and air pollution on incident of HTN.…”
Section: From Gwas To Prs For Htnmentioning
confidence: 99%
“…Currently, the anti-VEGF-A monoclonal antibody, bevacizumab, is approved as an effective adjunctive therapy for solid tumors [ 92 ]. However, severe hypertension is a common adverse effect of bevacizumab [ 93 ]. Regardless of whether Flt-1 or bevacizumab is used, local rather than systemic medical treatment may be more suitable for future clinical trials.…”
Section: The Mechanisms and Target Of Angiogenesis In Aa/admentioning
confidence: 99%
“…exceptionally high genetic risks for CHD 22 . In addition to individual prediction, polygenic scores have been used to model the effects of risk traits, including BMI 23 for hypertension and CHD, and systolic and diastolic blood pressure genetic risk for phenotypic hypertension or diagnose cardiovascular diseases 24,25,26 . A recent UK Biobank study examining BP and low-density lipoprotein polygenic scores found that, among those treated for hypertension, an increased SBP polygenic score was still associated with uncontrolled hypertension 27 .…”
Section: Introductionmentioning
confidence: 99%